2019
DOI: 10.3390/nano9081114
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Cytocompatibility of Bone Cement Enriched with Antibiotic, Nanosilver, and Nanocopper for Bone Regeneration

Abstract: Bacterial infections due to bone replacement surgeries require modifications of bone cement with antibacterial components. This study aimed to investigate whether the incorporation of gentamicin or nanometals into bone cement may reduce and to what extent bacterial growth without the loss of overall cytocompatibility and adverse effects in vitro. The bone cement Cemex was used as the base material, modified either with gentamicin sulfate or nanometals: Silver or copper. The inhibition of bacterial adhesion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 83 publications
2
19
0
Order By: Relevance
“…The present results are consistent with our previous study with human dental pulp stem cells and blood cells [26] and the research of others [71,72,73]. Thus, coating spacer with bone cement modified with antibiotic or nanosilver (up to 3%) does not deteriorate the overall biocompatibility of the material construct.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The present results are consistent with our previous study with human dental pulp stem cells and blood cells [26] and the research of others [71,72,73]. Thus, coating spacer with bone cement modified with antibiotic or nanosilver (up to 3%) does not deteriorate the overall biocompatibility of the material construct.…”
Section: Resultssupporting
confidence: 93%
“…In our studies, the effective surface antibacterial effect of NpAg-BC could be assumed. More detailed analysis regarding the bactericidal effectiveness of nanosilver was carried out in our previous research [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slane et al [24] proposed commercial bone cement containing commercial Ag nanoparticles (30–50 nm, surface-functionalized with polyvinylpyrrolidone) at different ratios (0.25%, 0.5%, and 1.0% w / w ) and demonstrated that Ag-nanoparticle-loaded samples were able to reduce the formation of S. aureus and S. epidermidis biofilms on their surface, even if they showed no effect towards planktonic cells. A good antimicrobial effect was also demonstrated by Wekwejt et al [25], introducing commercial Ag nanoparticles (50 nm, 1.5% and 3% w / w ) into Cemex formulations. Samples showed the inhibition of adhesion and growth of five different bacterial strains and displayed good cytocompatibility.…”
Section: Cement With Antibacterial Activity: Antibiotic-loaded Bonmentioning
confidence: 55%
“…The proposed system is characterized by a wide range of application possibilities, it is easy to use and also can eliminate the disadvantages of another methods of treatment such as, for example, titanium mesh, which is heavy, relatively expensive to produce and can cause soft tissue damage. Moreover, it was proposed that a modified bioactive bone cement be used, which was initially studied by the authors (Świeczko‐Żurek, ; Wekwejt et al, ; Wekwejt, Moritz, Świeczko‐Żurek, & Pałubicka, ). This material has bactericidal properties and, as a result, protects against infection.…”
Section: Introductionmentioning
confidence: 99%